Determinants of corruption in Latin America: A country-level analysis with a Bayesian approach - Flores Márquez, Héctor; Jiménez Gómez, Adrián (Estudios Económicos de El Colegio de México, 2025)
Corruption is a social phenomenon that has a profound effect in the Latin American region, for this reason, it is proposed to find the causes that contribute to its development. The Bayesian Model Averaging with Instrumental Variables (IVBMA) methodology is used to find robust determinants of corruption in 19 Latin American countries. 23 regressors are considered with observations from 2013 to 2020. The IVBMA carries out 8,388,608 models, in order to extract the most robust determinants. It is revealed that institutional and economic elements are better predictors of corruption in the region.